Improving UV-C stability in polypropylene through synergistic phenolic or hydroxylamine-based additives with UV absorbers - Marcos Vinícius Basaglia; Jessica Caroline Ferreira Gimenez; Manoel Gustavo Petrucelli Homem; Sandra Andrea Cruz; Lucas Henrique Staffa; Sílvia Helena Prado Bettini (eXPRESS Polymer Letters)
UV-C radiation (200–280 nm) is recognized for its effectiveness in disinfection, but it also induces degradation in polymeric materials such as polypropylene (PP), reducing their service life. Stabilizing additives are a viable approach to mitigating or delaying the degradation process. However, the chemical groups within these additives may adversely affect stabilization under UV-C exposure due to their potential to absorb the radiation. This study investigates the degradation of PP under UV-C radiation and evaluates the performance of stabilization systems containing phenolic antioxidants (Irganox 1010), hydroxylamine (Irgastab FS 042), and UV absorbers (Tinuvin 1577). PP films were exposed to UV-C radiation for 24, 48, and 96 h, corresponding to doses of 1000, 2000, and 4000 J/cm2. Degradation was assessed using size exclusion chromatography (SEC), parallel plate rheometry, infrared spectroscopy (FTIR), static water contact angle, and mechanical testing. The independent use of antioxidants or UV absorbers resulted in reduced carbonyl group formation relative to neat PP, but these were insufficient to prevent PP brittleness after 96 h of exposure. In contrast, the combined use of hydroxylamine or phenolic additives with UV absorbers effectively preserved PP ductility, allowing deformations exceeding 300% without fractures, indicating a synergistic effect.